Stent Thrombosis in Patients Treated with Ticagrelor in Acute Coronary Syndrome (ACS) Among Pakistani Population (Medical Forum Monthly, 2020)
Objective: To observe the stent thrombosis with Ticagrelor and to assess the frequency of main cardiovascular (CV) events (CV death, MI and Stroke) in patients treated with Ticagrelor after PCI (Stenting) during 24 weeks.Study Design: Observational studyPlace and Duration of Study: This study was conducted at the department of Cardialogy, Liaquat National Hospital, Karachi from March, 2020 to September, 2020.Materials and Methods: A total of 320 patients between the age of 18-75 year, presenting with acute coronary syndrome were included for this study. Demographic variables like age and gender were recorded. BMI, clinical features and history of previous diseases were also noted. Ticagrelor (Anplag®)90 mgbd was prescribed to the patients and was followed for 6 months for the occurrence of stent thrombosis, major cardiovascular events and adverse effects of Ticagrelor.Results: The outcomes of present study showed that there were total 4(1.2%) cases of stent thrombosis.The result in the present study also showed that overall there were 12(3.75%) deaths due to all causes of mortality. The most common adverse effect after taking Ticagrelor within 24-weeks was nausea found in 37(11.6%) and the least common side effect was bleeding in 4 (1.3%) cases. The other side effects including dyspnea and dizziness were also observed in 29(9.1%) and 32(10%) cases respectively.Conclusion: This study concludes that stent thrombosis is uncommon in a patient who receives anti-platelet therapy with Ticagrelor (Anplag®) 90 mg bd. A major prospective of Ticagrelor is the extra ordinary reduction in death among acute coronary syndrome patients.